Japanese - Islamic World Religious - Cultural Interactions: A Historical and Contemporary Perspective - Muhammad Adil Iqbal; Ashfaq Ahmed; Dr. Nurul Izzati Haji Jamil (Indonesian Journal for Islamic Studies, 2026)
Background: Although the interaction between Japan and the Islamic world has been extensively studied in historical and geopolitical contexts, there are still few consequences for comparative religious studies. In example, despite their similar focus on spiritual development, the relationship between Sufism and Zen Buddhism has not been thoroughly examined.Objectives: Through the themes of self-discipline, awareness, and transcendence, this research compares Sufi and Zen traditions and looks at Japanese Islamic connections within a civilizational framework.Methods: This study uses a qualitative comparative methodology based on religion studies, combining phenomenology, comparative hermeneutics, and civilizational analysis. Classical Sufi and Zen texts are examples of primary sources, which are bolstered by secondary historical and theoretical literature. A triadic framework that emphasizes self-discipline, awareness cultivation, and transcendental experience is used to organize the analysis.Results: The results show that Sufism and Zen share fundamental parallels in their approaches to disciplined practice and experiential transformation, despite little direct historical interaction. But their metaphysical underpinnings are very different; Zen is based on a non-theistic understanding of reality, whereas Sufism is based on a theistic framework.Conclusion: This study demonstrates that meaningful comparison between Sufism and Zen is possible at the level of practice and experience rather than doctrine. It contributes to comparative religious studies by offering a balanced framework that highlights both convergence and divergence, providing a relevant model for interreligious dialogue in a globalized context.